The pronunciation of English as a Lingua Franca: linguistic schizophrenia of users and speakers - Stanojević, Mateusz-Milan (Array, 2014)
One cannot help judging people according to their accent. For instance, we prefer historically powerful over less powerful groups based on their pronunciation (Lindemann 2005), and the in-group over the out-group (Dailey 2005). However, speakers of English as a Lingua Franca (ELF) – English used in international communication among non-native speakers – do not form an imagined community (Prodromou 2008), because there is no stable “horizontal comradeship” (Anderson 1991:7). This means that ELF is stratified (Stanojević and Josipović Smojver 2013) rather than monolithic (Jenkins 2006:161), and that attitudes towards it are constructed between individuals in particular communicative situations. One aspect of this is referred to as “linguistic schizophrenia” (Kachru 1977): being aware that one's non-native ELF pronunciation is a reality, all the while believing that one should strive towards a native-like pronunciation. This paper explores linguistic schizophrenia as a result of the ELF speaker's perceived status as a “learner” or a “user” in a given situation. It is a part of a larger study which used a range of qualitative and quantitative methodologies to ensure validity. We report on the results of two focus groups, one which predominantly focused on the ELF speakers' “learner” identity, and one which focused on the “user” identity. The results of the “learner” focus group show that the native speaker is seen as an authority figure, which is connected with the prestige of native accents. Imitating a native accent is not only related to correctness, but also a point of pride, and may sometimes stem from the belief that native speaker accents are easier to understand. As opposed to that, members of the “user” focus group are aware of the fact that certain native accents may be more difficult to understand than non-native speakers, although they do mention certain non-native Englishes as problematic in this respect too. They are aware that achieving a native-like pronunciation is a daunting, if not an impossible task. In other words, they realize that their production norm is based on international intelligibility, although they do not believe that this should be the teaching norm. Despite recognizing their pronunciation as non-native, they still seem to have to mediate that to themselves. These results confirm the appearance of linguistic schizophrenia, and indicate that in (research) situations when their “learner” identity is called up, ELF speakers prefer a normative approach to pronunciation based on native-speaker pronunciation primacy, whereas in cases when their “user” identity is called up, they prefer a non-normative approach. This is in line with a quantitative study performed on a Croatian sample (Josipović Smojver and Stanojević 2013). Still, the learner identity, along with its native-speaker primacy, necessarily comes up as part of judgments of one's own pronunciation (and the pronunciation of others) as users, perhaps due to the “model – learner” inequality inherent in the more traditional (non learner-centered) approaches.